Botulinum Toxin Type A (BOTOX) for Refractory Myofascial Pelvic Pain - ADELOWO, Amos (2013)
OBJECTIVE: To assess intralevator Botulinum toxin type A (Botox) injections for refractory myofascial pelvic pain with short tight pelvic floor. METHODS: Retrospective cohort study of all women with intralevator Botox injection (100-300 Units) from 2005 through 2010 for refractory myofascial pelvic pain. Primary outcomes were self-reported pain on palpation and symptom improvement. Secondary outcomes included post-injection complications and repeat injection. Pain was assessed during digital palpation of the pelvic floor muscles using a scale of 0-10, with 10 being the worst possible pain. Follow-up occurred at <6 weeks post-injection and again at ≥ 6 weeks. Data are presented as median (interquartile range) or proportion. RESULTS: Thirty-one patients met eligibility criteria; 2 were lost to follow up and excluded. Median age was 55.0 years (38.0-62.0). Before Botox injection, median pain score was 9.5 (8.0-10.0). Twenty-nine patients (93.5%) returned for the first follow-up visit; 79.3% reported improvement in pain, while 20.7% reported no improvement. Median pain with levator palpation was significantly lower than before injection (P<0.0001). Eighteen women (58.0%) had a second follow-up visit with a median pain score that remained lower than before injection (P<0.0001). Fifteen (51.7%) women elected to have repeat Botox injection; the median time to repeat injection was 4.0 (3.0-7.0) months. Three (10.3%) women developed de-novo urinary retention, 2 (6.9%) reported fecal incontinence and 3 (10.3%) reported constipation and/or rectal pain; all side effects resolved spontaneously. CONCLUSIONS: Intralevator injection of Botox demonstrates effectiveness in women with refractory myofascial pelvic pain with few, self-limiting adverse effects.